PERLINDUNGAN HAK ANAK DALAM PEMERIKSAAN PERKARA PERMOHONAN DISPENSASI KAWIN - Mudawamah Mudawamah (Negara dan Keadilan, 2021)
Jurnal dengan judul “Perlindungan Hak Anak Dalam Pemeriksaan Perkara Permohonan Dispensasi Kawin” ini berangkat dari permasalahan bagaimana bentuk perlindungan hak anak dalam pemeriksaan perkara permohonan dispensasi kawin dan bagaimanana implikasi hukum dispensasi kawin dalam rangka perlindungan hak anak. Penelitian ini bertujuan untuk menganalisis dan menjelaskan perlindungan hak anak dalam pemeriksaan perkara permohonan Dispensasi Kawin dan juga implikasi hukum Dispensasi Kawin dalam rangka perlindungan hak anak. Penelitian ini termasuk penelitian yuridis normatif. Penelitian ini menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Sumber bahan hukum dalam penelitian ini terdiri dari bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Analisis penelitian ini dilakukan dengan analisis deskripstif kualitatif. Berdasarkan hasil penelitian, dapat disimpulkan bahwa perlindungan hak anak selama proses pemeriksaan perkara permohonan Dispensasi Kawin mengacu pada UU Perkawinan dan juga Perma Nomor 5 Tahun 2019 tentang Pedoman Mengadili Permohonan Dispensasi Kawin. Adapun bentuk perlindungan hak anak dalam pemeriksaan perkara permohonan Dispensasi Kawin meliputi: 1) Diperiksa oleh Hakim Tunggal yang kompeten, 2) Memberikan rasa nyaman di persidangan, 3) Menghadirkan anak dalam proses pemeriksaan, 4) Hakim menghadirkan dan memberi nasihat kepada Orang Tua, Anak, Calon Suami/Isteri dan Orang Tua/Wali Calon Suami/Isteri, 5) Mengutamakan kepentingan terbaik untuk anak, dan 6) Pertimbangan hukum oleh hakim yang mewujudkan kepastian, kemanfaatan dan keadilan bagi anak. Permohonan Dispensasi Kawin menimbulkan implikasi hukum baik permohonan tersebut dikabulkan ataupun ditolak. Dalam memberikan pertimbangan hukum atas permohonan Dispensasi Kawin tersebut, hakim harus mengutamakan kepentingan terbaik bagi anak dengan mempertimbangkan moral, agama, adat dan budaya, aspek psikologis, aspek kesehatan, dan dampak yang ditimbulkan untuk mewujudkan kepastian, kemanfaatan dan keadilan bagi anak.Kata kunci: Perlindungan Hak Anak, Dispensasi Kawin The journal related to "The Protection of the Rights of the Child in Examination of Cases of Application for Marriage Dispensation" departs from the problem of how to protect children's rights in examining cases of applications for marriage dispensation and how are the legal implications of marriage dispensation in the context of protecting children's rights. This study aims to analyze and explain the protection of children's rights in examining cases of applications for marriage dispensation and also the legal implications of marriage dispensation in the context of protecting children's rights. This research is a normative juridical research. This study uses a statutory approach and a conceptual approach. The sources of legal materials in this study consist of primary legal materials, secondary legal materials and tertiary legal materials. The analysis of this research was carried out by means of a qualitative descriptive analysis. Based on the results of the research, it can be concluded that the protection of children's rights during the process of examining cases of marriage dispensation applications refers to the Marriage Law and also Supreme Court regulations Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. The forms of protection of children's rights in the examination of cases of application for Marriage Dispensation include: 1) The examination by a competent single judge, 2) Providing a sense of comfort at court, 3) Presenting children in the examination process, 4) The Judge presents and advises parents, children, candidate for husband / wife and parents / guardian of candidate husband / wife, 5) Prioritizing the best interests of the child, and 6) Legal considerations by the judge that realize certainty, benefit and justice for the children. An application for marriage dispensation has legal implications whether the application is granted or rejected. In providing legal considerations for the request for the marriage dispensation, the judge must prioritize the best interests of the child by considering the moral, religious, customary and cultural aspects, psychological aspects, health aspects, and the impact that is created to create certainty, benefit and justice for the child.Keywords: Protection of Children's Rights, Marriage Dispensation